Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1128/jb.157.3.703-707.1984
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium meliloti competitiveness and the alfalfa agglutinin

Abstract: We have isolated two types of isolates having identical colony morphologies from stock cultures of two different Rhizobium meliloti strains. One isolate was agglutinated at a high-dilution titer (HA, highly agglutinable) of the alfalfa agglutinin and was sensitive to phage F20, and the other was agglutinated at a lower agglutinin titer (LA) and was sensitive to phage 16B. All LA isolates from the original slant produced nodules on alfalfa earlier than did HA strains from the original slant. When these HA and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

1986
1986
1992
1992

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…Given such developmental constraints, one explanation for competitive ability might be that competitive strains are more efficient in nodule formation, either needing few cells to initiate infection or completing the complex sequence of infection events with minimal delay. This has been briefly considered by both Dowling and Broughton (9) and Hodgson and Stacey (15), while a positive relationship between traits indicative of efficient nodule formation and strain competitiveness has been reported for R. meliloti (14), R. leguminosarum biovar trifolii (27), and R. leguminosarum biovar phaseoli (24a). The present study examines the rela-Competition studies.…”
mentioning
confidence: 94%
“…Given such developmental constraints, one explanation for competitive ability might be that competitive strains are more efficient in nodule formation, either needing few cells to initiate infection or completing the complex sequence of infection events with minimal delay. This has been briefly considered by both Dowling and Broughton (9) and Hodgson and Stacey (15), while a positive relationship between traits indicative of efficient nodule formation and strain competitiveness has been reported for R. meliloti (14), R. leguminosarum biovar trifolii (27), and R. leguminosarum biovar phaseoli (24a). The present study examines the rela-Competition studies.…”
mentioning
confidence: 94%
“…Changes in susceptibility for phage due to alterations in cell wall polymers were observed also by Handelsman et al (7). They described a Rhizobium strain which has a low agglutination ability and is resistant to phage F20, whereas its phage-sensitive variant is highly agglutinable.…”
Section: Discussionmentioning
confidence: 63%
“…Several compounds, such as proteins and other polymers, are known to mask the phage receptor in bacteria (16,20,27). Any changes in these polymers may alter the susceptibility for phage and agglutination reaction with lectins (7).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified factors that contribute to competitiveness. These factors include motility (2,19), cell surface polysaccharides (12,28), and bacteriocin production (27). However, the importance of these factors for competitiveness in the field has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%